Good's syndrome with diffuse panbronchiolitis as the prominent manifestation: A case and literature review. Issue 12 (8th November 2021) - Luo, Tian; Wang, Lile; Fu, Daiyan; Hu, Ruicheng; Kong, Chunchu; Chen, Yunrong; Li, Xi
Abstract: Good's syndrome (GS) is characterized by thymoma combined with adult‐onset immunodeficiency. Diffuse panbronchiolitis (DPB) is a chronic inflammatory airway disease, which predominantly affects East Asians. Japanese scholars have reported extensively about GS combined with DPB or DPB‐like pulmonary manifestation. However, such reports are rare in China. We report here a case of GS in China with DPB as the prominent manifestation and carry out a literature review accordingly. Our review indicates that in adults with DPB‐like clinical manifestations, thymic lesions should be excluded and related immune function tests should be performed to exclude GS to avoid missed diagnosis and misdiagnosis. Abstract : We report here a case of Good's syndrome (GS) with diffuse panbronchiolitis (DPB) as the prominent manifestation and carry out a literature review accordingly. Japanese scholars have reported extensively about GS combined with DPB or DPB‐like pulmonary manifestation. However, such reports are rare in China; hence, the present report might help improve the understanding and diagnosis of such cases.